Single photon emission computed tomography in adrenoleukodystrophy: a case report - Dirik, Eray; Durak, Hatice; Eroğlu, Yasemen; Sayıt, Elvan; Büyükgebiz, Benal (The Turkish Journal of Pediatrics, 1996)
Adrenoleukodystrophy (ALD) is a genetic disorder leading to progressive dysfunction of the adrenal cortex and nervous system white matter. Accumulation of fatty acids in cerebral white matter results in some anatomical and functional changes which are detectable by imaging studies. Lately, single photon emission computed tomography (SPECT) has been suggested for evaluation of cerebral perfusion changes. In this report, magnetic resonance imaging (MRI) and SPECT neuroimaging of an eight-year-old boy with ALD are presented. SPECT revealed more extensive involvement than that demonstrated by MRI. Its role in early prediction of the extention of disease is stressed.
Keywords: adrenoleukodystrophy; magnetic resonance imaging; SPECT neuroimaging